Kompetensi Kepribadian Guru Dalam Pendidikan Digital: Kebutuhan dan Tantangan - Fadiltuzzahro; Lilik Sriyanti (Tematik: Jurnal Pendidikan Dasar Islam, 2025)
This research aims to identify the personality competencies required of teachers in the digital era, analyze the various challenges that arise, and examine the relevant forms of competence in the digital transformation process. Through the literature study method, the results of the study indicate that the digital space is characterized by a rapid flow of information, unlimited connectivity, and a visual-interactive culture that influences the way students think and behave. The digital generation tends to multitask and be adaptive, but is prone to fading social ethics, exposure to negative content, cyberbullying, and false information. Teachers are not only required to understand the material, but also to have digital literacy, pedagogical creativity, technological adaptability, and instilling digital ethics. It requires a stable personality, integrity, empathy, reflectiveness, and inspirational digital communication. Research confirms that digital teachers must be adaptive, ethical, and authoritative to guide the critical and responsible use of technology.